A Review on Comparison of Human Bite Marks in Forensic Images - Chandramouleeswaran, M; Puviarasan, N (International Journal of Computer Sciences and Engineering, 2022)
Human bite mark analysis is most demanding and complicated part of forensic dentistry, involving identification of assailant by comparing record of their dentition with record of bite mark left on a victim. Bite marks are unique to individual such as distance and angles between teeth, missing, and teeth fillings. This type of impression evidence can be left in the skin of a victim. Following the identification of an injury as a bite mark, the comparison of the pattern produced to a suspect’s dentition is very vital. This article contains the current methods of comparison of human bite marks using different methods and technologies.